Capsaicin-Induced Changes in Electrical Pain Perception Threshold Can Be Used to Assess the Magnitude of Secondary Hyperalgesia in Humans. Issue 11 (26th April 2020) - Hughes, Sam W; Basra, Meirvaan; Chan, Calvin; Parr, Callum; Wong, Felyx; Gomes, Sofia; Strutton, Paul H
Abstract: Objectives: Areas of secondary hyperalgesia can be assessed using quantitative sensory testing (QST). Delivering noxious electrocutaneous stimulation could provide added benefit by allowing multiple measurements of the magnitude of hyperalgesia. We aimed to characterize the use of electrical pain perception (EPP) thresholds alongside QST as a means by which to measure changes in pain thresholds within an area of secondary mechanical hyperalgesia. Methods: EPP and heat pain thresholds (HPTs) were measured at five distinct points at baseline and following 1% capsaicin cream application, one within a central zone and four within a secondary zone. Areas of secondary mechanical hyperalgesia were mapped using QST. In a further 14 participants, capsaicin-induced reduction in EPP thresholds was mapped using a radial lines approach across 24 points. Results: There was a reduction in EPP threshold measured at the four points within the secondary zone, which was within the mapped area of mechanical secondary hyperalgesia. The magnitude of secondary hyperalgesia could be split into a mild (∼4% reduction) and severe (∼21% reduction) area within an individual subject. There was no reduction in HPT within the secondary zone, but there was a reduction in both HPT and EPP threshold within the primary zone. EPP mapping revealed differences in the magnitude and spread of hyperalgesia across all subjects. Conclusions: Measuring capsaicin-induced reduction in EPP thresholds can be used to map hyperalgesic areas in humans. This semi-automated approach allows rapid assessment of the magnitude of hyperalgesia, both within an individual subject and across a study population.